Strategi Peningkatan Penyaluran Kredit Berdasarkan Analisis Kinerja Keuangan dan Faktor Eksternal BPR di Kabupaten Bogor - yuliningtyas, priyantika; purwanto, budi (Jurnal Manajemen dan Organisasi, 2016)
Bank Perkreditan Rakyat (BPR) is a financial institution that is growing currently as having a role in the funding of small and medium businesses. In Bogor district, there are 25 BPRs who each has different strengths and weaknesses. Based on the cluster analysis, it is obtained three clusters of BPR which are grouped based on their ability to manage assets, its non-performing loan risks, likuidity, profitability and the operating expenses of BPR. Based on the clustering of BPRs and analysis of internal and external factors of each BPR group, it has found operational strategy to increase credit disbursement  and lowering non-performing loan risks. The strategy for group “A” BPRs is to develop the market, to increase in BPRs facilities, to implement a system of shared-responsibility credit, and to increase precautionary in the credit disbursement. Strategy for group “B” BPRs is to increase the credit interest, to improve customer service and facilities, market penetration and running partners with the common bank. At last, the strategy for the group “C” BPRs is to increase promotion, improving services, increase the amount of credit disbursement and improving the quality of human resources.